Lixo zero? Uma pesquisa-ação na co-construção de uma solução territorial para os resíduos sólidos urbanos - Marcelo Alves de Souza (2021)
Would it be possible nowadays to think of a city that fully incorporates the waste it produces in its productive and reproductive spheres - that is, a zero waste city - as a real utopia? Without intending to definitively answer this question, which depends on social practices and the engagement of collective actors, this work provides, however, in the scale in which it is located, elements for a qualified reflection on it. As a result of action-research undertaken since 2012, in the work of supporting and advising associations and cooperatives of waste pickers (ACs), we seek to report and analyze the development process of the Lixo Zero Santa Tereza Network. An experience that, by integrating popular recycling, urban agroecology and territorial governance, emerges as an alternative to the privatization of waste and to destructive technologies in waste management, understood as concrete threats to the work of waste pickers and their organizations in Brazil. More specifically, we seek to deepen the understanding of the development processes 1) of the services produced under the aforementioned Network, 2) of the spaces in the territory that support these services, and 3) of the territorialized cooperative ecosystem engendered by operators, beneficiaries and technical advisors, which co-construct this territorial solution. These dynamics are analyzed within some theoretical and conceptual frameworks, such as the Functionality and Cooperation Economy, design for social innovation and the Common, more specifically, the development of public nature services (such as waste management) as institutions of the common. We investigate, from real cases, how the development of horizontal and transversal cooperation – bases for the co-construction of the territorial solution – takes place, and the difficulties encountered, as well as the role, in this construction, of different "dialogical devices" of collective listening and reflection instituted and mobilized within the ecosystem. In the end, proposing the concept of "urban laboratory of Common policy", we seek to reflect on how this experience and similar ones, of experimenting with new territorial services, built in cooperation with civil society, can contribute to the development of new and innovative approaches for public waste management, which are able to respond, in a more pertinent way, to the challenges posed.